1988
DOI: 10.1271/bbb1961.52.1619
|View full text |Cite
|
Sign up to set email alerts
|

Induction of precocious metamorphosis by 1,5-disubstituted imidazoles with a non-terpene chain.

Abstract: Wehave already reported the anti-juvenile hormone (anti-JH) activity of a number of 1,5disubstituted imidazoles with a JH-like terpene chain in silkworm, Bombyxmori, larvae.1'2) These imidazole compounds induced unequivocal precocious metamorphosis, which was clearly recognized as a JH-deficiency symptom.31 Tworepresentative compounds, name-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1990
1990
2011
2011

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…Isopropyl imidazole, neopentyl imidazole, 2,6-bis(3-butylimidazol-1-yl)pyridine bromide, 2,6-bis(3-isopropylimidazol-1-yl)pyridine bromide, and 2,6-bis(3isopropylimidazol-2-thione-1-yl)pyridine were prepared as reported previously [20][21][22][23][24] as were BNA + and BNAH [25]. NMR spectra were recorded at 25 o C on a Bruker Avance 300 MHz NMR spectrometer.…”
Section: General Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…Isopropyl imidazole, neopentyl imidazole, 2,6-bis(3-butylimidazol-1-yl)pyridine bromide, 2,6-bis(3-isopropylimidazol-1-yl)pyridine bromide, and 2,6-bis(3isopropylimidazol-2-thione-1-yl)pyridine were prepared as reported previously [20][21][22][23][24] as were BNA + and BNAH [25]. NMR spectra were recorded at 25 o C on a Bruker Avance 300 MHz NMR spectrometer.…”
Section: General Proceduresmentioning
confidence: 99%
“…were accomplished following Scheme 1. The alkyl imidazoles were either prepared following known routes or were commercially available [20,22]. Different R groups were employed because Crabtree has reported that modification of such substituents affects the solubility and catalytic activity of the metal complexes [23].…”
Section: Syntheses and Spectroscopymentioning
confidence: 99%
“…II A number of AJHA have so far been found such as precocene-2 (P-2), 2 1 ftuoromevalonate, 31 ethyl 4-[2-(tert-butylcarbonyloxy)butoxy ]benzoate (ETB), ethyl (E)-3-methyl-2-dodecenoate 3045 (EMD), 4 1 benzyl-1,3-benzodioxole (J-2710), 5 • 6 1 imidazoles (KK-22, 7 1 KK-42, 8 1 KK-110), 9 1 and dichloroallyl hexanoate.101 These compounds induce precocious metamorphosis in a restricted number of insect species. The aim of this study was to evaluate the effects of different types of AJHA (P-2, J-2710 and KK-110) on the postembryonic development of Neobellieria bullata (Parker) (Diptera: Sarcophagidae).…”
mentioning
confidence: 99%